척수마취중 Diazepam - fentanyl 동시투여가 환자의 심혈관반응 및 동맥혈 산소포화도 ( SaO2 ) 에 미치는 영향 - 허경원; Kyung Won Huh; 김동옥; Dong Ok Kim; 김건식; Keon Sik Kim; 최영규; Young Koo Choi; 권무일; Moo Il Kwon (Korean journal of anesthesiology, 1992)
Combining benzodiazepine with opioid has been used for analgesia and sedation during spinal anesthesia, but many authors have warned that combined administration of these drugs produces potent drug interaction that places patients at high risk for hypoxemia and apnea. This study was undertaken to observe the effect of combined use of diazepam with fentanyl on hemodynamic response and change in SaO in twenty healthy adult patients undergone elective surgery with spinal anesthesia. All of the patients were divided into the control and experimental group, and whom spinal anesthesia with 0.5% tetracaine the 12 mg and epinephrine 0.2 mg, were performed. To the control(Group I) and experimental group(Group 2) the combined dose of diazepam 0. 075 mg/kg with fentanyl 1 μg/kg, and diazepam 0.15 mg/kg with fentanyl 2 μg/kg, were given, respectively, by intravenous injection 1 hour after spinal anesthesia started. Blood pressure, heart rate and SaO₂ of the two groups were compared at the time before administration of study drugs and 1 min, 2 min, 2 min, 4 min, 5 min, 10 min, 30 min and 60 min after administration of study drugs. The results were as follows. 1) SaO₂ was significantly decreased in group 2 than Group 1 after study drugs were administed intravenously. 2) In both group, decrease in SaO₂ was significant at the first 5 minutes after intravenous administration of study drugs. 3) SaO₂ fell to 90% of the control value after the administration of study drugs in 6 patients of Group 2(60%). 4) Hemodynamic changes after intravenous administration of study drugs were statistically significant but not so clinically in both group. We concluded that combined intravenous administration of benzodiazepine and opioid under spinal anesthesia requires the careful monitoring of hemodynamic response and ventilatory status continuosly with those monitoring devices already in use and pulse oximeter. Availiability of skilled anesthesiologists for airway management and administration of supplemental oxygen are very important in combined intravenous administration of benzodiazepine and opioid